ANALISIS KERJA SAMA ANTARA PETANI DAN PENGEPUL SAYUR DI DESA BENGKILU KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG - Indah Khoirun Nisa; Izhar Salim; Stella Prancisca (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to determine cooperation in the form of mutual cooperation, bargaining, and co-optation between farmers and vegetable collectors at Bengkilu Village, Tujuh Belas District, Bengkayang Regency. The research approach used is a descriptive qualitative approach. Data collection techniques used are observation, interview, and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The analysis in this study is presented descriptively using 6 informants, 3 informants as vegetable farmers and 3 informants as vegetable collectors. The results of this study indicate that the cooperation between farmers and vegetable collectors in the form of mutual cooperation, bargaining, and co-optation has been implemented. It is proved that there are forms of help given by vegetable collectors to vegetable farmers, such as transporting vegetable crops directly to vegetable farmers' gardens using transport vehicles such as pick-ups, lending money to vegetable farmers if farmers need money for the benefit of their families, and there are the process of bargaining the selling price of vegetables to vegetable collectors, as well as discussions held by vegetable collectors to vegetable farmers about how to plant vegetables properly and correctly in order to get good quality vegetables.Keywords: Cooperation, Farmers, Vegetable Collectors